2017
DOI: 10.1159/000484437
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Proactive Treatment of Depression in Lewy Body Dementias: The Impact on Hippocampal Neurogenesis and Cognition in a Post-Mortem Study

Abstract: Objective: To examine the impact of selective serotonin reuptake inhibitors (SSRIs) and depression on neurogenesis and cognition in dementia with Lewy bodies (DLB) and Parkinson disease dementia (PDD). Methods: Late-stage progenitor cells were quantified in the subgranular zone (SGZ) of the hippocampal dentate gyrus of DLB/PDD patients (n = 41) and controls without dementia (n = 15) and compared between treatment groups (unmedicated, SSRIs, acetyl cholinesterase inhibitors [AChEIs], combined SSRIs and AChEIs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Regarding the management of depression in DLB patients, serotoninergic-targeted therapy would be an option based on individual response. Furthermore, selective serotonin reuptake inhibitor treatment may even be associated with increased hippocampal neurogenesis and preservation of cognition in DLB/PDD patients according to a recent study [ 27 ]. Extrapyramidal symptoms Previous studies mostly revealed no benefits or mild improvement with levodopa treatment in motor symptoms of DLB patients [ 28 , 29 ].…”
Section: Recommended Management Of Dlbmentioning
confidence: 99%
“…Regarding the management of depression in DLB patients, serotoninergic-targeted therapy would be an option based on individual response. Furthermore, selective serotonin reuptake inhibitor treatment may even be associated with increased hippocampal neurogenesis and preservation of cognition in DLB/PDD patients according to a recent study [ 27 ]. Extrapyramidal symptoms Previous studies mostly revealed no benefits or mild improvement with levodopa treatment in motor symptoms of DLB patients [ 28 , 29 ].…”
Section: Recommended Management Of Dlbmentioning
confidence: 99%
“…On the other hand, Boldrini and colleagues [4] In contrast to Sorrells and colleagues' observations, Boldrini and colleagues were able to detect all of the immature and mature cell types in the adult human DG as shown in previous other studies [2,7,8]. Furthermore, they did not observe a substantial decline in the number of these cells with age.…”
mentioning
confidence: 74%
“…Individuals with DLB are at high risk of developing major depression as part of the syndrome, with depression being present from an early stage (Fujishiro et al 2015) with a significant impact on quality of life (Gatt et al 2017; McKeith et al 2017). Depression in DLB correlates with α-synuclein pathology and Lewy bodies in late onset MDD found in older populations, indicating that α-synuclein pathology may be a significant factor in development of MDD in older individuals (Nunes et al 2022).…”
Section: Discussionmentioning
confidence: 99%